Mentoring The Implementation of Learning Management System in Realizing Islamic Smart School - Chusnul Muali; Abu Yazid Albustomi (Al-Qalam Institute, 2025)
This study aims to explore the process and impact of mentoring the implementation of a Learning Management System (LMS) in realizing the Islamic Smart School model in junior high schools. The digital transformation of education in rural Indonesia faces significant barriers, including limited teacher digital literacy and a lack of culturally and religiously contextualized learning materials. The study used the Asset-Based Community Development (ABCD) framework to assess school resources, followed by capacity-building workshops, mentoring, and co-development of digital content integrating Islamic values. The results showed a significant increase in teacher confidence and proficiency in using the LMS platform, with LMS confidence increasing from 24% to 88%, and ability to integrate Islamic values into digital content from 15% to 80%. Teachers also reported increased motivation and ownership of digital pedagogy, with 84% expressing high motivation to continue using the LMS tool. The establishment of an LMS Clinic and Virtual Support Forum fostered ongoing peer support, contributing to the sustainability of digital pedagogy. This research contributes to the understanding of how digital transformation in Islamic education can be successfully integrated with religious values through a structured and participatory mentoring program.